Fatigue in a population-based cohort of patients with inflammatory bowel disease 20 years after diagnosis: The IBSEN study. (4th March 2017) - Huppertz-Hauss, Gert; Høivik, Marte Lie; Jelsness-Jørgensen, Lars-Petter; Opheim, Randi; Henriksen, Magne; Høie, Ole; Hovde, Øistein; Kempski-Monstad, Iril; Solberg, Inger Camilla; Jahnsen, Jørgen; Hoff, Geir; Moum, Bjørn; et al.
Abstract: Objective: Fatigue is a major concern for patients with ulcerative colitis (UC) and Crohn's disease (CD), but evidence from population-based studies regarding fatigue in long-standing inflammatory bowel disease (IBD) patients is scarce. Our aims were to assess fatigue scores and the prevalence of chronic fatigue in IBD patients 20 years after diagnosis and to identify variables associated with fatigue in this cohort. Methods: Twenty years after diagnosis, patients from a cohort with incident IBD were invited to a follow-up visit that included a structured interview, a clinical examination, laboratory tests and the Fatigue Questionnaire (FQ). Fatigue scores were obtained, and factors associated with fatigue were assessed via linear and logistic regression analyses. Results: Of the 599 invited patients, 440 (73.5%) completed the FQ. Among those with active disease, we found significantly higher fatigue scores than among those with quiescent disease (fatigue scores: UC 17.1 versus 12.4, p < .001, and CD 17.5 versus 13.3, p < .001). The fatigue scores of those with quiescent disease were comparable with those of the reference population. Chronic fatigue was more frequent among IBD patients than in the reference population. Factors associated with fatigue included self-perceived disease activity, poor sleep quality, anxiety and depression. Conclusion: At 20 years after IBD diagnosis, fatigue scores were higher and chronic fatigue was more frequent among IBD patients with active disease than in the reference population and among those with quiescent IBD. Subjectively perceived disease activity, sleep quality, anxiety and depression were associated with fatigue in IBD patients.